RP-HPLC Estimation of Exemestane in Tablet Dosage Form - Vijaya Lakshmi, M.; Seshagiri Rao, J.V.L.N.; Lakshmana Rao, A. (Asian Journal of Chemistry, 2010)
A rapid, sensitive and precise HPLC method was developed for the estimation of exemestane in pure and tablet dosage forms. Separation of the drug was achieved on a reverse phase C8 column using a mobile phase consisting of water and methanol in the ratio of 50:50 v/v. The flow rate was 1 mL/min and the detection wavelength 249 nm. The linearity was found in the range of 25-150 μg/mL with a correlation coefficient of 0.9998. The proposed method was validated for its sensitivity, linearity, accuracy and precision. This method can be employed for routine quality control analysis of exemestane in tablet dosage forms.